A bird's eye view approach: linking optimism and career planning in millennials of an emerging economy. (24th August 2020) - Bharti, Teena; Rangnekar, Santosh
The study aims to test the construct of optimism (positive future expectancies) and career planning in the students born in millennial era. The study investigated the gender differences in a sample of 381 students enrolled in a postgraduate program. The study adopted a cross-sectional survey-based research design and employed hierarchical regression technique to establish the relationship. Further, the study used Hayes-PROCESS approach to test the moderating role of gender. The results revealed that the millennial students have high levels of optimism and females are more optimistic in nature as compared to male students owing to various environmental and societal reasons. Furthermore, the male-female ratio is increasing in millennial population over a period of time. The research emphasised the role of an optimistic outlook in order to plan ahead as career planning is an ongoing process reflecting the effects of the environmental uncertainties. Hence, optimism should be cultivated in order to promote the competence and skill-building events which would help in enhancing the productivity resulting in better understanding of workplace and life at large. The work supplements the existing literature on outcome expectancies by adding to the social cognitive career theory.